2014
DOI: 10.1016/j.agee.2013.11.025
|View full text |Cite
|
Sign up to set email alerts
|

The trade-off between food production and greenhouse gas mitigation in Norwegian agriculture

Abstract: Norwegian agriculture makes a disproportionate contribution to the country's emissions of greenhouse gases (GHG) relative to its contribution to gross domestic product (GDP)-a picture that is repeated globally. Using a detailed economic model we examine what impacts an assumed 30 per cent cut in GHG emissions from agriculture may have on food production. We find that a CO 2 tax on agricultural activity would result in a reduction of agricultural production, particularly of GHG-intensive commodities such as bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 9 publications
0
14
1
Order By: Relevance
“…The work also showed significant environmental co-benefits from reductions in soil erosion and leakage of nutrients to water supplies, at all carbon prices. A similar approach applied to Norway (Blandford, Gaasland and Vårdal, 2014a) showed that a significant reduction in heavily-supported beef and sheepmeat production is needed to achieve a 30% reduction in emissions, but that changes in dairy policy (relaxation of production quotas) could facilitate mitigation in dairy production by increasing productivity. Mitigation would also be facilitated if farmers were rewarded for undertaking carbon sequestration activities (agroforestry) on marginal land, thereby avoiding significant contraction in agricultural output, in line with the government's policy objective of preserving agricultural activity in the country.…”
Section: Determining Cost-effective Mitigation Optionsmentioning
confidence: 99%
“…The work also showed significant environmental co-benefits from reductions in soil erosion and leakage of nutrients to water supplies, at all carbon prices. A similar approach applied to Norway (Blandford, Gaasland and Vårdal, 2014a) showed that a significant reduction in heavily-supported beef and sheepmeat production is needed to achieve a 30% reduction in emissions, but that changes in dairy policy (relaxation of production quotas) could facilitate mitigation in dairy production by increasing productivity. Mitigation would also be facilitated if farmers were rewarded for undertaking carbon sequestration activities (agroforestry) on marginal land, thereby avoiding significant contraction in agricultural output, in line with the government's policy objective of preserving agricultural activity in the country.…”
Section: Determining Cost-effective Mitigation Optionsmentioning
confidence: 99%
“…These facts have motivated many researches to search for solutions targeted at lowering the emissions (Franks and Hadingham, 2012;Beukes et al, 2010;Dalgaard et al, 2011;Johnson et al, 2007;Vergé et al, 2007;Guo and Zhou, 2007;Smith et al, 2007;Glenk et al, 2014;Blandford et al, 2014;Eory et al, 2013;Winiwarter et al, 2014 andSnyder et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The concrete climate actions taken to achieve this goal are disputed and remain unclear. A potential conflict of GHG emission reductions and other agricultural policy objectives has so far been discussed at the national level [2,3]. This paper contributes to this knowledge gap by questioning the extent to which the regional distribution of agricultural activity and changes in farm size affect GHG emissions from agriculture.…”
Section: Introductionmentioning
confidence: 99%